2009
DOI: 10.1039/b819479c
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule in metal cluster cages: H2@Mgn (n = 8 to 10)

Abstract: Core-shell isomers of small magnesium clusters "doped" with a hydrogen molecule are theoretically studied and predicted to be weakly stable or metastable for different sizes of the system, allowing a low-temperature release of hydrogen. Evolution of H(2) inside Mg(n) is followed from the molecular species to two H atoms. Among properties analyzed are equilibrium geometries, dissociation energies, charge distributions, vertical energies of electronic excitation, ionization and electron attachment, and vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 12 publications
2
57
0
Order By: Relevance
“…Several other materials include aluminum nitride (AlN) nanostructures [4], transition‐metal‐doped boron nitride systems [5], alkali‐metal‐doped benzenoid [6], boron–Li clusters [7] fullerene clusters [8], bare as well as light metal and transition‐metal‐coated boron buckyballs, B 80 [9], and magnesium clusters [10], which have been further confirmed on both experimental and theoretical bases to serve as unique hydrogen storage materials. Recently, Chattaraj et al [11] have demonstrated that small to medium metal cluster moieties involving the cationic Li 3+ and Na 3+ and neutral Mg n and Ca n ( n = 8–10) cages, analogous to the metastable hydrogen‐stacked Mg n clusters [12] reported earlier, have got a relatively fair aptitude of trapping hydrogen in both atomic and molecular forms.…”
Section: Introductionmentioning
confidence: 99%
“…Several other materials include aluminum nitride (AlN) nanostructures [4], transition‐metal‐doped boron nitride systems [5], alkali‐metal‐doped benzenoid [6], boron–Li clusters [7] fullerene clusters [8], bare as well as light metal and transition‐metal‐coated boron buckyballs, B 80 [9], and magnesium clusters [10], which have been further confirmed on both experimental and theoretical bases to serve as unique hydrogen storage materials. Recently, Chattaraj et al [11] have demonstrated that small to medium metal cluster moieties involving the cationic Li 3+ and Na 3+ and neutral Mg n and Ca n ( n = 8–10) cages, analogous to the metastable hydrogen‐stacked Mg n clusters [12] reported earlier, have got a relatively fair aptitude of trapping hydrogen in both atomic and molecular forms.…”
Section: Introductionmentioning
confidence: 99%
“…However, several materials like AlN nanostructures (3), transition-metal doped BN systems (4), alkali-metal doped benzenoid (5), and fullerene clusters (6), bare as well as light metal and transition-metal coated boron buckyballs, B 80 (7), and magnesium clusters (8) have been exercised experimentally and theoretically as capable storage material for hydrogen. Again, owing to the considerable ability of MgH 2 as a hydrogen-storage material, Mg-clusters doped with H 2 molecule have been theoretically investigated and found to be weakly stable or metastable depending on the cluster size (9). Giri et al (10) have recently demonstrated that small to medium metal clusters involving the trigonal, cationic Li 3 + and Na 3 + rings, and the neutral Mg n and Ca n [ n =8–10] cages, analogous to the metastable hydrogen-stacked Mg n clusters (9) can be executed for trapping hydrogen effectively in both atomic and molecular forms.…”
mentioning
confidence: 99%
“…Again, owing to the considerable ability of MgH 2 as a hydrogen-storage material, Mg-clusters doped with H 2 molecule have been theoretically investigated and found to be weakly stable or metastable depending on the cluster size (9). Giri et al (10) have recently demonstrated that small to medium metal clusters involving the trigonal, cationic Li 3 + and Na 3 + rings, and the neutral Mg n and Ca n [ n =8–10] cages, analogous to the metastable hydrogen-stacked Mg n clusters (9) can be executed for trapping hydrogen effectively in both atomic and molecular forms.…”
mentioning
confidence: 99%
“…[1][2][3] Numerous other materials, like aluminum nitride (AlN) nanostructures [4] , transition-metal doped boron nitride (BN) systems [5] , alkali-metal doped benzenoid [6] and fullerene clusters [7] , bare as well as light metal and transition-metal coated boron buckyballs, B 80 [8] , and magnesium clusters [9] have been confirmed both experimentally and theoretically to serve as potential hydrogen-storage materials. Further, based on a theoretical study invoking the metastability of hydrogen-stacked Mg n clusters [10] , Chattaraj et al [11] have very recently demonstrated that a host of small to medium metal cluster moieties involving Li 3 + , Na 3 + , Mg n and Ca n (n = 8-10) cages have got a fair capability of trapping hydrogen in both atomic and molecular forms. The stability of the aforesaid all-metal systems has been attributed to the existence of an aromaticity criterion in the metallic rings which was assessed through the rationale of nucleus independent chemical shift (NICS) [12] .…”
Section: Introductionmentioning
confidence: 99%